Analog-to-Digital Conversion - Pelgrom, Marcel J.M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
The design of an analog-to-digital converter or digital-to-analog converter is one of the most fascinating tasks in micro-electronics. In a converter the analog world with all its intricacies meets the realm of the formal digital abstraction. Both disciplines must be understood for an optimum conversion solution. In a converter also system challenges meet technology opportunities. Modern systems rely on analog-to-digital converters as an essential part of the complex chain to access the physical world. And processors need the ultimate performance of digital-to-analog converters to present the results of their complex algorithms. The same progress in CMOS technology that enables these VLSI digital systems creates new challenges for analog-to-digital converters: lower signal swings, less power and variability issues. Last but not least, the analog-to-digital converter must follow the cost reduction trend. These changing boundary conditions require micro-electronics engineers to consider their design choices for every new design. Analog-to-Digital Conversion discusses the different analog-to-digital conversion principles: sampling, quantization, reference generation, nyquist architectures and sigma-delta modulation. It also presents an overview of the state-of-the-art in this field and focuses on issues of optimizing accuracy and speed while reducing the power level. A lot of background knowledge and practical tips complement the discussion of basic principles, which makes Analog-to-Digital Conversion also a reference for the experienced engineer.
Components and Definitions -- Sampling -- Sample and Hold -- Quantization -- Reference Circuits -- Digital-to-Analog Conversion -- Analog-to-Digital Conversion -- Sigma-delta Modulation -- Characterization and Specification -- Technology -- System Aspects of Conversion.
Keywords: Engineering; Computer network architectures; Systems engineering; Engineering; Circuits and Systems; Solid State Physics; Spectroscopy and Microscopy; Computer Systems Organization and Communication Networks